Lower semicontinuity of monotone functionals in the mixed topology on Cb - Max Nendel (Finance and Stochastics, 2024)
Abstract The main result of this paper characterises the continuity from below of monotone functionals on the space Cbof bounded continuous functions on an arbitrary Polish space as lower semicontinuity in the mixed topology. In this particular situation, the mixed topology coincides with the Mackey topology for the dual pair (Cb,ca), where cadenotes the space of all countably additive signed Borel measures of finite variation. Hence lower semicontinuity in the mixed topology is for convex monotone maps Cb→Requivalent to a dual representation in terms of countably additive measures. Such representations are of fundamental importance in finance, e.g.~in the context of risk measures and superhedging problems. Based on the main result, regularity properties of capacities and dual representations of Choquet integrals in terms of countably additive measures for 2-alternating capacities are studied. Moreover, a well-known characterisation of star-shaped risk measures on L∞is transferred to risk measures on Cb. In a second step, the paper provides a characterisation of equicontinuity in the mixed topology for families of convex monotone maps. As a consequence, for every convex monotone map on Cbtaking values in a locally convex vector lattice, continuity in the mixed topology is equivalent to continuity on norm-bounded sets.
Additional information: C02;C65
Keywords: 330; Risk measure; Monotone functional; Choquet integral; Continuity from below; Lower semicontinuity; Mixed topology; Mackey topology; Star-shaped